2021
DOI: 10.1177/09673911211001277
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and rheological properties of carbon black based conductive polymer composites prior to and after annealing

Abstract: The effect of annealing on the electrical and rheological properties of polymer (poly (methyl methacrylate) (PMMA) and polystyrene (PS)) composites filled with carbon black (CB) was investigated. For a composite with CB content near the electrical percolation threshold, the formation of conductive pathways during annealing has a significant impact on electrical conductivity, complex viscosity, storage modulus and loss modulus. For the annealed samples, a reduction in the electrical and rheological percolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Recently, Gao et al [ 53 ] presented interesting studies about the effect of thermal treatment (200 °C, 2 h) on the electrical and rheological properties of poly(methyl methacrylate) and polystyrene composites filled with carbon black. The main finding showed that annealing treatments resulted in the decrease in the electrical conductivity of conductive polymer composites, which can be attributed to the breakdown of the unstable conductive pathways and the formation of secondary CB aggregates, which is in agreement with our results.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gao et al [ 53 ] presented interesting studies about the effect of thermal treatment (200 °C, 2 h) on the electrical and rheological properties of poly(methyl methacrylate) and polystyrene composites filled with carbon black. The main finding showed that annealing treatments resulted in the decrease in the electrical conductivity of conductive polymer composites, which can be attributed to the breakdown of the unstable conductive pathways and the formation of secondary CB aggregates, which is in agreement with our results.…”
Section: Resultsmentioning
confidence: 99%